Risk-based reliability analysis and generic principles for risk reduction - Todinov, Michael T.
This book has been written with the intention to fill two big gaps in the reliability and risk literature: the risk-based reliability analysis as a powerful alternative to the traditional reliability analysis and the generic principles for reducing technical risk.